2000
DOI: 10.1038/80671
|View full text |Cite
|
Sign up to set email alerts
|

Remembering episodes: a selective role for the hippocampus during retrieval

Abstract: Some memories are linked to a specific time and place, allowing one to re-experience the original event, whereas others are accompanied only by a feeling of familiarity. To uncover the distinct neural bases for these two types of memory, we measured brain activity during memory retrieval using event-related functional magnetic resonance imaging. We show that activity in the hippocampus increased only when retrieval was accompanied by conscious recollection of the learning episode. Hippocampal activity did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

73
531
12
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 814 publications
(618 citation statements)
references
References 33 publications
73
531
12
2
Order By: Relevance
“…Thus, activation in the hippocampus and PHG was clearly selective for source retrieval success, with perirhinal cortex demonstrating a more complex pattern. Eldridge et al [28], using the "remember/know" paradigm, observed a conceptually similar pattern [28]. In that study, only correct endorsements accompanied by subjective reports of remembering resulted in hippocampal activation.…”
Section: Neurocognitive Correlates Of Source Recognitionmentioning
confidence: 64%
See 3 more Smart Citations
“…Thus, activation in the hippocampus and PHG was clearly selective for source retrieval success, with perirhinal cortex demonstrating a more complex pattern. Eldridge et al [28], using the "remember/know" paradigm, observed a conceptually similar pattern [28]. In that study, only correct endorsements accompanied by subjective reports of remembering resulted in hippocampal activation.…”
Section: Neurocognitive Correlates Of Source Recognitionmentioning
confidence: 64%
“…Thus, correct and incorrect source recognition should yield differential hippocampal activation. In contrast, from one perspective [28,35], retrieval success effects should not be observed within the hippocampus during recency recognition, as such judgments in the current paradigm are hypothesized to be largely non-recollective.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…The retrieval attempt, in which the participant mounts a strategic effort to remember, elicits activity in the PFC (Buckner & Wheeler, 2001). 6 Activity in the hippocampus (Eldridge, Knowlton, Furmanski, Bookheimer, & Engel, 2000;Henson et al, 1999) and the posterior parietal cortex (Wagner et al, 2005) correlates with successful retrieval. 7 Neural areas also track the retrieval of information across the different sensory domains differently, such that the recollection of a visual scene may result in the activity of visual cortices even in the absence of visual stimulation (M. E. Wheeler, Petersen, & Buckner, 2000).…”
Section: Extinction Learning In Humansmentioning
confidence: 99%